Green apple baked snacks functionalized with edible coatings of methylcellulose containing Lactobacillus plantarum - Tavera Quiroz, María José (2015)
The aim of the present work was to develop a healthy snack as a vehicle of probiotic bacteria. Apple snacks were coated with methylcellulose films containing fructooligosaccharides and Lactobacillus plantarum CIDCA 83114. Dehydration of the snacks at 60 °C for 50 min allowed obtaining a product with water content, crispness and visual aspect similar to those before applying the film-forming solution, without major detrimental effects for microorganisms. Sensory attributes of coated snacks were evaluated by an experienced sensory panel, receiving good scores in taste (6.5 ± 0.6), color (7.7 ± 0.4), texture (7.2 ± 0.4) and overall acceptability (7.2 ± 0.3). Storage of the snacks at 20 °C and 60% RH caused only a mild decrease in the bacterial cultivability after 90 days (1.4 log CFU/g), and a significant number of bacteria were still alive after the simulated gastric (5.5 × 106 ± 0.7 × 106 CFU/g) and intestinal (1.0 × 106 ± 0.4 × 106 CFU/g) digestions of the stored samples. The force–deformation curves showed a typical pattern of brittle materials up to 90 days of storage.The Tg followed a similar trend, in accordance with the constant moisture content. An organoleptically attractive food product was obtained which after 90 days of storage presented a high load of cultivable lactobacilli (2.0 × 108 ± 0.7 × 108 CFU/g). This concentration is well above the minimum considered necessary (106–107 CFU/g) to obtain the benefits of probiotic consumption.